Determination of Compassion and Compassion Fatigue in Intensive Care Nurses - Ahmet Özan MSc; Hatice Polat PhD (SAGE Publishing, 2024)
Introduction Compassion is defined as the sadness felt by a living thing or a person due to a negative situation. Compassion fatigue describes emotional, physical, social and spiritual exhaustion or a decrease in these feelings. The concept of compassion, which is at the center of nursing, may be related to compassion fatigue in nurses. Objective The aims of the study were to determine the level of compassion fatigue and compassion among intensive care nurses and to examine the relationship between them. Methods This study was conducted through descriptive research and cross-sectional survey. The population of the research consisted of intensive care nurses from two hospitals in Turkey. Since the universe is accessible, the sample selection method was not used ( n = 182). Demographic data form, Compassion Fatigue sub-dimension of the Professional Quality of Life Scale and Compassion Scale were used in the study. Results The mean score of the nurses' compassion fatigue was 15.86 ± 7.22, and compassion was 72.21 ± 7.28. There was a moderate negative relationship between compassion and compassion fatigue ( r  = −.405). It was determined that the nurses' compassion was at a moderate level and their compassion fatigue was at a low level. Conclusion It can be assumed that ICU nurses' compassion is at a medium level and their compassion fatigue is at a low level. It was established that as the compassion level of the nurses increased, the level of compassion fatigue decreased. Developing a sense of compassion in nurses working in intensive care units can reduce compassion fatigue.